2017
DOI: 10.1002/pola.28901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkyl side chains positioning and presence of fused aromatic units in the backbone of low‐bandgap diketopyrrolopyrrole copolymers on the optoelectronic properties of organic solar cells

Abstract: The systematic optimization of the chemical structure of low-bandgap (LBG) donor-acceptor polymeric semiconductors is a challenging task for which accurate guidelines are yet to be determined. Several different structural and molecular parameters are crucial ingredients for obtaining LBG polymers that simultaneously possess high power conversion efficiencies, good processability in common organic solvents, and enhanced stability in organic photovoltaic devices. In this work, we present an extensive structure-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The polymers were synthesized via Stille coupling from a DPP-bithiophene monomer with each corresponding bithiophene ditin compound (see Materials and Methods). , In our previous study, it was found that the highly flexible thiophene-thiophene (T-T) dihedral in the isoindigo-bithiophene-based conjugated polymer is critical to forming wavy, helical polymer chain conformation. Such polymer chains further stack in a staggered fashion to form chiral helical fibrils in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The polymers were synthesized via Stille coupling from a DPP-bithiophene monomer with each corresponding bithiophene ditin compound (see Materials and Methods). , In our previous study, it was found that the highly flexible thiophene-thiophene (T-T) dihedral in the isoindigo-bithiophene-based conjugated polymer is critical to forming wavy, helical polymer chain conformation. Such polymer chains further stack in a staggered fashion to form chiral helical fibrils in solution.…”
Section: Resultsmentioning
confidence: 99%
“…3) the tail-to-tail connectivity has been reported to help increase the backbone planarity for DPP-based polymer in comparison with the head-to-head one. [51] This article is protected by copyright. All rights reserved.…”
Section: Resultsmentioning
confidence: 99%
“…chains. [51,54] This shallower HOMO is helpful for efficient doping because of the electron transfer between the polymers with polar side chains and the oxygen with low-lying LUMO energy level. [40] In order to get an insight into the structural and electronic properties of both polymers, we also performed the theoretical investigation and calculated the optimized This article is protected by copyright.…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized aromatic systems bearing alkyl chains are important synthons for compounds with applications in materials science, molecular electronics, and catalysis . The self-assembly of organic or organometallic derivatives on metal surfaces often utilizes long alkyl chains, which ensure the alkyl-driven packing of self-assembled monolayers (SAMs) .…”
Section: Introductionmentioning
confidence: 99%